MOBILE PHONE REGULATION: THE EFFECTS OF PROHIBITING HANDSET BUNDLING IN FINLAND. (20th February 2018) - Hazlett, Thomas W; Oh, Sarah; Skorup, Brent
Abstract: Vertical restrictions have theoretically ambiguous efficiency effects. Marketplace evidence is, therefore, required to reveal the presence of anticompetitive foreclosure. The bundling of mobile phones with cellular network service offers one such market test. One EU member, Finland, prohibited tying arrangements for mobile service and mobile handsets in wireless broadband markets, and then cleanly ended this prohibition in April 2006. We compare the growth in Finnish third-generation (3G) uptake against other European markets using quarterly data from first quarter 2006 through fourth quarter 2012. An output effects model adjusting for market-specific factors suggests 3G penetration growth in Finland increased substantially following market reform.